Sustainability Reporting from the Perspective of GRI Standards, ISSB/IFRS S1 and S2, and OJK Regulations in Indonesia - Fanti Mariana Siburian; Elda Sianturi; Keren Eoudia Sitompul; Febrison Marbun; Hicca Maria Gandi Putri Aruan (Manunggal Halim Jaya, 2026)
This study aims to analyze the development of sustainability reporting based on the GRI Standards, ISSB/IFRS S1 and IFRS S2, and the Financial Services Authority (OJK) regulations in Indonesia, using PT Pertamina (Persero) as a case study. This research applies a descriptive qualitative approach through literature review and comparative analysis of global sustainability reporting frameworks and national regulations. The findings indicate that sustainability reporting has shifted from a voluntary practice to a more standardized and integrated reporting system. The GRI Standards emphasize impact materiality, focusing on corporate impacts on the economy, environment, and society. In contrast, IFRS S1 and IFRS S2 emphasize financial materiality, focusing on sustainability-related risks and opportunities that affect enterprise value, particularly climate-related issues. In Indonesia, OJK Regulation No. 51/POJK.03/2017 plays an important role in encouraging mandatory sustainability reporting for financial service institutions, issuers, and public companies. The case of PT Pertamina indicates that the company has implemented sustainability reporting relatively comprehensively; however, it still faces challenges in measuring Scope 3 emissions, integrating sustainability risks with enterprise value, improving ESG data quality, and harmonizing its reporting practices with global standards. This study highlights the importance of integrating GRI, IFRS S1/S2, and OJK regulations to enhance the transparency, credibility, and comparability of sustainability reporting in Indonesia.